Pengembangan Sistem Informasi Geografis Berbasis Website (WEBGIS) Untuk Simulasi Pemetaan Daerah Genangan Banjir Rob Menggunakan Metode Neighbourhood Analysis (Studi Kasus : Pantai Utara Kota Surabaya) - Taufik Brillian Nur; Alfi Nur Rusydi; Satrio Agung Wicaksono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The North Coast Area of Surabaya City is an area that has great potential for the occurrence of tidal floods. The magnitude of the potential because of that area has a sea level rise as high as 5.47 mm per year within 64 years. In addition, by looking at the geographical condition of Surabaya, which consists of 80.72% of the area with low land, also adds threats to the occurrence of tidal flood disasters of the region. Based on the data that recorded in 2010, there has been a tidal flood in part area of Surabaya City that has caused the loss of property, submerged industrial area, disturbed activity of harbor and submerged part of the farm area located in District of Benowo, Asemrowo and Krembangan. Therefore, by looking at the magnitude of the impact caused by the tidal flood, it is needed a Geographic Information System based website (WEBGIS) that can simulate the inundation area of the rob and can explain the kind of landuse that affected by the tidal flood in that area. Related methods used to create the inundation area using the Neighborhood Analysis function found in ILWIS application. Based on the simulation results in each scenario shows that the most dominant landuse affected is farming with minimum impact of 155.7 ha and maximum impact of 374 ha. As for the results of system testing shows with black-box testing certainly functional system can run 100% with system compatibility rate of 73%.